2001
DOI: 10.1097/00003246-200105000-00037
|View full text |Cite
|
Sign up to set email alerts
|

Variation in therapy and outcome for pediatric head trauma patients

Abstract: Therapies and outcomes vary across pediatric intensive care units that care for children with head injuries. Increased use of seizure medications may be warranted based on data from this observational study. Large randomized controlled trials of seizure prophylaxis in children with head injury have not been conducted and are needed to confirm the findings presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
2
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 38 publications
1
58
2
3
Order By: Relevance
“…45,46,55,56 Absence of insurance coverage, so-called "self-pay" status, is a particularly adverse factor. 24,43,55,56 In the pediatric age range, however, trauma patients admitted without insurance often acquire retroactive Medicaid coverage, and this coverage is registered in discharge data if the hospital stay is long enough. Patients with no insurance who die of their injuries tend to have relatively short lengths of stay in the hospital and may fail to acquire Medicaid coverage before discharge data are registered.…”
Section: Discussionmentioning
confidence: 99%
“…45,46,55,56 Absence of insurance coverage, so-called "self-pay" status, is a particularly adverse factor. 24,43,55,56 In the pediatric age range, however, trauma patients admitted without insurance often acquire retroactive Medicaid coverage, and this coverage is registered in discharge data if the hospital stay is long enough. Patients with no insurance who die of their injuries tend to have relatively short lengths of stay in the hospital and may fail to acquire Medicaid coverage before discharge data are registered.…”
Section: Discussionmentioning
confidence: 99%
“…Large prospective randomized clinical trails are essential to compare the efficacy of different strategies [32,37,38,39,40]. These are not easy to perform in children with severe TBI since the number of children treated at each center is low.…”
Section: Discussionmentioning
confidence: 99%
“…27 These investigators also found that neurologists and neurosurgeons differed in the intensity with which they approached the same type of clinical problem within one institution, again highlighting the variable care that patients may receive according to where and by whom they are cared for. 27 Others have found influences on outcome according to whether patients are admitted to a general or to a neurosurgical ICU 28 or whether surgical intervention is early or delayed, 29 in the use of induced hypothermia, seizure medications, paralytic agents, 30 use of intracranial monitoring, 30,31 or according to physician prediction of severely impaired future cognitive function. 32 …”
Section: Predicting Mortalitymentioning
confidence: 99%